Aprendizagem Baseada em Equipes aplicada em Astronomia no 8° Ano do Ensino Fundamental - Dobre Ferreira, Jose Eduardo; Voelzke, Marcos Rincon (Educação, Escola & Sociedade, 2024)
To teach, to learn, and to assess are three processes that can occur simultaneously. The pedagogical proposal presented in this work suggests the use of Team-Based Learning (TBL) as a methodology for teaching the concepts of Astronomy proposed in the Earth and Universe Thematic Unit of the National Common Curricular Base (BNCC) for the 8th year of Elementary School, which involves the knowledge objects Sun, Earth, and Moon. The literature review takes into account the structure of TBL and formative assessment as an indicator of learning since the aim of this article is to situate the conjectures of TBL and propose a practice that articulates it with the theme Earth and Universe, besides highlighting the importance of self-assessment and peer assessment as guiding factors in this process.